The utilization of drug–polymer interactions for improving the chemical stability of hot-melt extruded solid dispersions. (25th October 2013) - Guo, Zhefei; Lu, Ming; Li, Yongcheng; Pang, Huishi; Lin, Ling; Liu, Xu; Wu, Chuanbin
Abstract: Objective: Interactions between drugs and polymers were utilized to lower the processing temperature of hot-melt extrusion (HME), and thus minimize the thermal degradation of heat-sensitive drugs during preparation of amorphous solid dispersions. Methods: Diflunisal (DIF), which would degrade upon melting, was selected as a model drug. Hydrogen bonds between DIF and polymeric carriers (PVP K30, PVP VA64, hydroxypropyl methylcellulose and Soluplus) were revealed by differential scanning calorimetry and Fourier transform infrared spectroscopy. The hot-melt extruded solid dispersion was characterized by powder X-ray diffraction (XRD), scanning electron microscopy (SEM) and high-performance liquid chromatography (HPLC). Key findings: The results of hot-stage polar microscopy indicated that DIF was dissolved in molten polymers at 160°C, much lower than the melting point of DIF (215°C). At this temperature, amorphous solid dispersions were successfully produced by HME, as confirmed by XRD and SEM. The related impurities in amorphous solid dispersions detected by HPLC were lower than 0.3%, indicating that thermal degradation was effectively minimized. The dissolution of DIF from amorphous solid dispersions was significantly enhanced as compared with the pure crystalline drug. Conclusion: This technique based on drug–polymer interactions to prepare chemically stable amorphous solid dispersions by HME provides an attractive opportunity for development of heat-sensitive drugs.